Electrospinning of SnO2-TiO2 nanofiber/nanorod composites for uses as electron transport layers in flexible perovskite solar cells - Methawee Nukunudompanich; Kamonchanok Roongraung; Kanyanee Sanglee; Wassana Lekkla; Surawut Chuangchote (My University, 2024)
In perovskite solar cells (PSCs), the most commonly used electron transport layers (ETLs) are titanium dioxide (TiO2) and tin oxide (SnO2). The problem with SnO2 is that its conduction band does not match that of perovskites, while TiO2's photocatalytic nature can destroy perovskite materials. Additionally, these ETLs are typically applied in the form of nanoparticles. Electrospinning was used to produce composite nanofibers or nanorods of SnO2-TiO2 to improve the photovoltaic performance of flexible PSCs, which are required for flexible electronic devices. SnO2-TiO2 nanofibers or NRs as ETLs assist perovskites in harvesting light, separating excitons, extracting and collecting electrons, blocking holes, and preventing perovskites from decomposing and forming defects. PSCs containing SnO2-TiO2 nanoparticles have been produced. From the J-V characteristics of flexible-PSCs, the use of SnO2-TiO2 nanofibers improved the power conversion efficiency of the solar cells. A higher current density was obtained. This occurs because the 1D structure allows for more freely moving electrons. Comparing SnO2 nanoparticles and TiO2 nanofibers, an SnO2-TiO2 layer provides superior charge mobility and helps improve strength of the bonding at the perovskite/ITO interface. It is superior to SnO2 NPs and TiO2 nanofibers in reducing surface recombination.
Keywords: Nanorod; Electrospinning; Titanium Dioxide; Indium tin oxide; Perovskite Materials and Applications